Sediment Ammonia-Oxidizing Microorganisms in Two Plateau Freshwater Lakes at Different Trophic States - Yang, Yuyin; Zhang, Jingxu; Zhao, Qun; Zhou, Qiheng; Li, Ningning; Yilin Wang; Xie, Shuguang; Yong Liu (MICROBIAL ECOLOGY, 2016)
Both ammonia-oxidizing archaea (AOA) and bacteria (AOB) can contribute to ammonia biotransformation in freshwater lake ecosystems. However, the factors shaping the distribution of sediment AOA and AOB in plateau freshwater lake remains unclear. The present study investigated sediment AOA and AOB communities in two freshwater lakes (hypertrophic Dianchi Lake and mesotrophic Erhai Lake) on the Yunnan Plateau (China). A remarkable difference in the abundance, diversity, and composition of sediment AOA and AOB communities was observed between Dianchi Lake and Erhai Lake. AOB usually outnumbered AOA in Dianchi Lake, but AOA showed the dominance in Erhai Lake. Organic matter (OM), total nitrogen (TN), and total phosphorus (TP) might be the key determinants of AOB abundance, while AOA abundance was likely influenced by the ration of OM to TN (C/N). AOA or AOB community structure was found to be relatively similar in the same lake. TN and TP might play important roles in shaping sediment AOA and AOB compositions in Dianchi Lake and Erhai Lake. Moreover, Nitrososphaera-like AOA were detected in Dianchi Lake. Nitrosospira- and Nitrosomonas-like AOB were dominant in Dianchi Lake and Erhai Lake, respectively. Sediment AOA and AOB communities in Dianchi Lake and Erhai Lake were generally regulated by trophic state.